Analisis Usahatani Pertanian Lahan Kering Melalui Integrasi Pertanian Dan Ternak Di Kabupaten Lombok Utara, Provinsi Nusa Tenggara Barat - Nuzuly Ilmia Cerminand; Ulfa Nurwiana; Mai Rizali (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2024)
The development of the agricultural sector is the mainstay of economic development. Empowerment of land resources as a basis for agricultural activities should receive more emphasis and attention from the government and other related parties. For this reason, strategic steps are needed to build public opinion and the government that dry land is the hope for the future of agricultural development to increase food security. The study used a descriptive method. The data collection technique used a survey technique. This study was conducted in North Lombok Regency, precisely in Bayan District, which was determine4d by "purposive sampling" with consideration of Bayan District. The results of the study showed that there were 7 types of planting and livestock patterns applied by respondent farmers in the dry land area of ​​Bayan District, North Lombok Regency with a combination of plant types that varied quite a lot between planting patterns, namely corn, rice, peanuts and cassava. Each planting pattern is integrated with livestock. Of the 7 planting patterns, there are 3 dominant planting patterns carried out by farmers, namely, the corn + livestock planting pattern as much as 40%, then the rice + livestock planting pattern (26.25%) and 16.25% for the rice + corn + livestock planting pattern. The cropping and livestock pattern that provides the highest income at the research location is rice + corn + livestock (X6) of 10,995,510.00 per hectare per year and the lowest income is in the peanut + livestock planting pattern (X4) of 2,808,721.60 per hectare per year.